2016
DOI: 10.1016/j.jpsychires.2016.02.012
|View full text |Cite
|
Sign up to set email alerts
|

Perception of faces in schizophrenia: Subjective (self-report) vs. objective (psychophysics) assessments

Abstract: Objectives Face perception impairment in schizophrenia has been demonstrated, mostly through experimental studies. How this laboratory-defined behavioral impairment is associated with patients’ perceptual experience of various faces in everyday life is however unclear. This question is important because a first-person account of face perception has direct consequences on social functioning of patients. In this study, we adapted and administered a self-reported questionnaire on narrative perceptual experience o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 37 publications
0
3
0
Order By: Relevance
“…A great variety of studies show changes in the visual processing of patients with schizophrenia and depression. Among those are altered perceptual organization (Steven et al, 2020;Panton, Badcock, & Badcock, 2016;Silverstein & Keane, 2011), face perception and recognition (Frassle et al, 2020;Marosi, Fodor, & Csukly, 2019;Stroud et al, 2018;Chen & Ekstrom, 2017;Berg et al, 2016;Maher, Ekstrom, Holt, Ongur, & Chen, 2016;McBain, Norton, & Chen, 2010;Silverstein et al, 2014;Vakhrusheva, et al, 2014), Psicol. Pesqui.…”
Section: Palabras Clavementioning
confidence: 99%
“…A great variety of studies show changes in the visual processing of patients with schizophrenia and depression. Among those are altered perceptual organization (Steven et al, 2020;Panton, Badcock, & Badcock, 2016;Silverstein & Keane, 2011), face perception and recognition (Frassle et al, 2020;Marosi, Fodor, & Csukly, 2019;Stroud et al, 2018;Chen & Ekstrom, 2017;Berg et al, 2016;Maher, Ekstrom, Holt, Ongur, & Chen, 2016;McBain, Norton, & Chen, 2010;Silverstein et al, 2014;Vakhrusheva, et al, 2014), Psicol. Pesqui.…”
Section: Palabras Clavementioning
confidence: 99%
“…Yet women with SZ perform generally better on emotion recognition tasks 49,50 . SZ patients not only exhibit aberrant facial affect recognition, but also deficient face processing such as face recognition, visual scanning of faces, and unfamiliar face matching [51][52][53][54] . Deficits appear to refer to assessment of the spatial relationship between facial features as well as holistic face perception [55][56][57][58][59] .…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the relationship between identity recognition impairments and symptoms has not been widely studied, and evidence is mixed. Two studies have reported a negative correlation between identity recognition performance in schizophrenia and both positive and negative symptoms 47,48 while several report correlations with negative symptoms only 26,45,[49][50][51] . To date, no studies have assessed symptom correlates with identity processing using dynamic stimuli.…”
Section: Introductionmentioning
confidence: 99%